An assisted structured reflection on life events and life goals in advanced cancer patients: Outcomes of a randomized controlled trial (Life InSight Application (LISA) study). (February 2019) - Kruizinga, Renske; Scherer-Rath, Michael; Schilderman, Johannes BAM; Hartog, Iris D; Van Der Loos, Jacoba PM; Kotzé, Hantie P; Westermann, Anneke M; Klümpen, Heinz-Josef; Kortekaas, Francesco; Grootscholten, Cecile; Bossink, Frans; Schrama, Jolanda; et al.
Background: Diagnosis and treatment of incurable cancer as a life-changing experience evokes difficult existential questions. Aim: A structured reflection could improve patients' quality of life and spiritual well-being. We developed an interview model on life events and ultimate life goals and performed a randomized controlled trial to evaluate the effect thereof on quality of life and spiritual well-being. Design: The intervention group had two consultations with a spiritual counselor. The control group received care as usual. EORTC QLQ-C15-PAL and the FACIT-sp were administered at baseline and 2 and 4 months after baseline. Linear mixed model analysis was performed to test between-group differences over time. Participants: Adult patients with incurable cancer and a life expectancy ⩾6 months were randomized in a 1:1 ratio to the intervention or control group. Results: A total of 153 patients from six different hospitals were included: 77 in the intervention group and 76 in the control group. Quality of life and spiritual well-being did not significantly change over time between groups. The experience of Meaning/Peace was found to significantly influence quality of life ( β = 0.52, adj. R 2 = 0.26) and satisfaction with life ( β = 0.61, adj. R 2 = 0.37). Conclusion: Although our newly developed interview model was well perceived by patients, we were not able to demonstrate a significant difference in quality of life and spiritual well-being between groups. Future interventions by spiritual counselors aimed at improving quality of life, and spiritual well-being should focus on the provision of sources of meaning and peace.